The image of the master in the film "seeking forrester" - William l. Perdomo Vanegas; Tito Pérez Martínez; Alfonso Soriano Espinosa; Wilson Trujillo Agudelo (Corporación Universitaria Minuto de Dios, 2007)
This article derives from the research work of the same name, which was conceived in the Bachelor of Arts Education at Uniminuto as a macro- project that responds to questions made from the Specific Didactics Research. The article presents a brief introduction to the systems significance, then offers a justification for research that is based on a theoretical foundation on the semiotics of cinema and, in turn, takes up significant contributions as author Umberto Eco, Roland Barthes , Christian Metz, Jean Marie Klinkenberg, among others. Finally, describes some of the results revealed in the investigative process and its findings, taking as text analysis of the film Finding Forrester directed by Gus Van Saint.